Perilaku Organisasi Lembaga Pelatihan Dan Kursus Educourse.id Cabang Surakarta - Maryani, Desi Nur Aristia; Kisworo, Bagus (Universitas Mataram, 2025)
This study aims to describe organizational behavior and its influencing factors at the Educourse.id Training Institute, Surakarta Branch. Organizational behavior is a crucial element in improving the effectiveness and efficiency of non-formal institutions. The research method used is a qualitative approach with data collection techniques including in-depth interviews, participatory observation, and documentation. The main informants consist of the branch head an teaching staff, while internship alumni serve as supporting informants. The results show that the organizational structure is lean but fuctional, although some staff members carry multiple responsibilities. The leadership style is participtive and transformational, as reflected in open communication and moral support for employees. Work motivation is largely intrinsic, but external incentives still need improvement. The work culture reflects values of togetherness, cooperation, and responsibility, which strengthen loyalty and job satisfaction. Factors such as leadership, communication, work structure, and organizational culture significantly influence the behavior of staff, the branch head, and even interns. The studey concludes that synergy among these organizational elements contributes to increased productivity and performance quality, although certain aspect still require optimization to achieve more optimal results.